2018
DOI: 10.1177/0972150918811701
|View full text |Cite
|
Sign up to set email alerts
|

Stylized Facts of High-frequency Financial Time Series Data

Abstract: High-frequency financial time series data have an ability to define market microstructure and are helpful in making rational real-time decisions. These data sets carry unique characteristics and properties which are not available in low-frequency data; with that high-frequency data also create more challenges and opportunities for econometric modelling and financial data analysis. So it is essential to know the features and the facts related to the high-frequency time series data. In this article, we provide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…He went on to demonstrate how these statistical qualities invalidate a large number of the statistical methodologies commonly used to study financial data sets and discussed some of the statistical issues that arise in each situation. [15] investigated the features and stylized facts presented by the S&P CNX Nifty futures index's high-frequency financial time series data. They found that the majority of stylized facts were connected to observable empirical behaviors, distributional features, autocorrelation functions, and the seasonality of high-frequency data.…”
Section: Related Researchmentioning
confidence: 99%
“…He went on to demonstrate how these statistical qualities invalidate a large number of the statistical methodologies commonly used to study financial data sets and discussed some of the statistical issues that arise in each situation. [15] investigated the features and stylized facts presented by the S&P CNX Nifty futures index's high-frequency financial time series data. They found that the majority of stylized facts were connected to observable empirical behaviors, distributional features, autocorrelation functions, and the seasonality of high-frequency data.…”
Section: Related Researchmentioning
confidence: 99%
“…Before estimation of the model, we must ensure that the data series is stationary (Shakeel & Srivastava, 2019). The ADF test (Dickey & Fuller, 1979) and the KPSS test (Kwiatkowski et al, 1992) is employed on the return data of the indices for the purpose.…”
Section: Stationary Variablesmentioning
confidence: 99%
“…Time series analysis is a statistical analysis method based on time series data for forecasting technology trends [85]. Time series data consist of an independent variable representing a time point and a dependent variable representing the frequency that can predict the future trend [86,87]. Among the models for analyzing time series data, the ARMA model is used as a representative [88,89].…”
Section: Time Series Analysismentioning
confidence: 99%